Spirituality in the Workplace: Enhanced Job Satisfaction Through Employee Well-being and Work-life Balance - Nikensari, Galuh Amilia; Yudhistira, Putu Gde Arie (Jurnal Manajemen Teori dan Terapan| Journal of Theoretical and Applied Management, 2024)
Objective: This study examines the relationship between workplace spirituality and job satisfaction mediated by employee well-being and moderated by work-life balance in the travel industry. Design/Methods/Approach: The data was collected using a questionnaire using purposive sampling. A total of 415 respondents working in conventional travel agent services participated in the study. Data analysis was performed using the Partial Least Square Structural Equation Model (PLS-SEM) via outer and inner models using SmartPLS 4. Findings: This study identifies that workplace spirituality positively has a direct and indirect impact on job satisfaction with the mediating effect of employee well-being and the moderating effect of work-life balance.  Originality/Value: The study provides new insights by examining both the direct and indirect impacts of workplace spirituality on job satisfaction within the travel agent industry. The study also identifies the moderating effect of work-life balance and the mediating effect of employee well-being formulated into a comprehensive model. Practical/Policy implication: This study provides managerial implications, suggesting managers can leverage workplace spirituality as a competitive advantage. Managers can enhance employees' job satisfaction by implementing well-being programs that consider employees' spiritual needs and work-life balance.